Ilhas interdisciplinares de racionalidade promovendo aprendizagem ativa - Moro, Elisiane da Costa (My University, 2015)
This work was developed within the research area "Educational Foundations and Strategies in Science and Mathematics Teaching" which aims: to investigate, evaluate and implement educational strategies in the light of education foundations. The objective of this study is to evaluate the use of the methodology "Interdisciplinary Islands of Rationality" about the theme "The electrical discharges in Brazil" in high school students’ learning. This proposal also aims to promote active learning in investigative and interdisciplinary environment through the development of an Interdisciplinary Island of Rationality (IIR). It also seeks to motivate students to study and understand Science and Mathematics challenging them to an investigative behavior. The research problem met the following question: can the Interdisciplinary Islands of Rationality promote active learning, interdisciplinarity and investigative attitude of high school students, as well as to develop Scientific and Technological Literacy (STL)? In the academic year of 2013, a IIR was applied in the Physics course to a class of third year of high school in a public school in Caxias do Sul, state of Rio Grande do Sul, in the third quarter of the school year as a pilot project and, applied again with the same theme in the first semester of the school year of 2014 with another third grade class of high school in the same school. This work was developed based on the proposal of Gerard Fourez that aims to provide to the students a Scientific and Technological Literacy, considering the need to make scientific contents meaningful for students, as well as useful for their lives. The learning theory chosen to support the evidence of the occurrence of learning by the students due to the application of the methodology was the Theory of Meaningful Learning by David Ausubel. Both in 2013 as in 2014, students demonstrated willingness to learn, actively participating in the activities that were suggested during the development of the IIR. Students had the opportunity to analyze and discuss the main consequences caused by the electrical discharges in Brazil, from the social, economic, environmental and scientificpoint of view. This phenomenon is in constant study by researchers of our country. Studies of the National Institute for Space Research (INPE) show that 57 million electrical discharges fall per year in Brazil, a world record. The development of the IIR encouraged the investigative behavior and the research, promoting the use of digital technologies and proposing the contextualization and the interdisciplinarityin a simple and natural way, taking into account the previous knowledge of students. They reached the goals of Scientific and Technological Literacy according to the perspective of the methodology, demonstrating mastery of the situation, autonomy in the production of knowledge and good communication of the thought situation. The students attempted to relate the scientific content with the situations experienced in their daily lives. The analysis of the observations and the productions of the students has shown that they were more active and creative in their learning process, managing to appropriate of the content about the theme in an interdisciplinary way. Students also showed evidences of a meaningful learning according to Ausubel’s theory.
Este trabalho foi desenvolvido dentro da linha de pesquisa "Fundamentos e Estratégias Educacionais no Ensino de Ciências e Matemática" que tem por objetivo: investigar, avaliar e pôr em prática estratégias educacionais, à luz dos fundamentos da educação. O objetivo deste trabalho é avaliar a utilização da metodologia “Ilhas Interdisciplinares de Racionalidade” em torno do tema “As descargas elétricas no Brasil” na aprendizagem de estudantes de Ensino Médio. Esta proposta pretende ainda promover a aprendizagem ativa em ambiente investigativo e interdisciplinar por meio da construção de uma Ilha Interdisciplinar de Racionalidade (IIR). Busca também motivar os estudantes a estudar e compreender as Ciências e a Matemática desafiando-os a um comportamento investigativo. O problema de pesquisa veio ao encontro do seguinte questionamento: As Ilhas Interdisciplinares de Racionalidade podem promover a aprendizagem ativa, a interdisciplinaridade e a atitude investigativa dos estudantes do Ensino Médio, assim como desenvolver a Alfabetização Científica e Tecnológica (ACT)? No ano letivo de 2013, uma IIR foi aplicada na disciplina de Física com uma turma de terceiro ano do Ensino Médio em uma escola estadual de Caxias do Sul, no estado do Rio Grande do Sul, no terceiro trimestre do ano letivo como um projeto-piloto e reaplicada com o mesmo tema no primeiro semestre do ano letivo de 2014 com outra turma de terceiro ano do Ensino Médio da mesma escola. Este trabalho foi desenvolvido com base na proposta de Gerard Fourez na perspectiva de proporcionar aos estudantes uma Alfabetização Científica e Tecnológica, observada a necessidade de tornar os conteúdos científicos significativos para os estudantes, bem como úteis para suas vidas. A teoria de aprendizagem escolhida para fundamentar as evidências de ocorrência de aprendizagem por parte dos estudantes devido à aplicação da metodologia foi a Teoria da Aprendizagem Significativa de David Ausubel. Tanto em 2013 quanto em 2014, os estudantes demonstraram predisposição para aprender, participando ativamente das atividades que foram sugeridas no decorrer do desenvolvimento da IIR. Os estudantes tiveram a oportunidade de analisar e discutir sobre as principais consequências causadas pelas descargas elétricas no Brasil, do ponto de vista social, econômico, ambiental e científico. Este fenômeno está em constante estudo por pesquisadores do nosso país. Estudos do Instituto Nacional de Pesquisas Espaciais (INPE) mostram que caem 57 milhões de descargas elétricas por ano no Brasil, um recorde mundial. O desenvolvimento da IIR incentivou o comportamento investigativo e a pesquisa, promovendo a utilização de tecnologias digitais e propondo a contextualização e a interdisciplinaridade de maneira simples, com naturalidade, levando em conta os conhecimentos prévios dos estudantes. Os mesmos atingiram os objetivos da Alfabetização Científica e Tecnológica de acordo com a perspectiva da metodologia, demonstrando domínio da situação estudada, autonomia na produção do conhecimento e facilidade na comunicação da situação pensada. Os estudantes procuraram relacionar os conteúdos científicos com as situações vivenciadas no seu cotidiano. A análise das observações e das produções dos estudantes permitiu verificar que os mesmos foram mais ativos e criativos no processo de ensino aprendizagem, conseguindo apropriar-se dos conteúdos em torno do tema de maneira interdisciplinar. Os estudantes demonstraram também evidências de uma aprendizagem significativa de acordo com a teoria de Ausubel.
Keywords: Abordagem interdisciplinar do conhecimento na educação; Aprendizagem; Ensino médio - Caxias do Sul (RS); Interdisciplinary approach in education; Learning; High school - Caxias do Sul (Brazil)